A new method to estimate fuel surface area-to-volume ratio using water immersion - Rego, Francisco (1998)
A fast, simple, low cost and general technique for estimating fuel surface area-to-volume ratio is presented. The technique requires particle density, the determination of fuel weight before and after immersion in water and the theoretical thickness of the adsorbed water pellicle that is assumed constant. Estimates by the technique were consistent and in good agreement with published surface area-to-volume ratios for the same fuels obtained through other methods, and its performance was judged appropriate for current fire behaviour modelling needs. This water immersion technique was applied to various shrubs and trees grown in Portugal. Limitations and possibilities for improvement of the newly developed technique are discussed.